2015
DOI: 10.4314/ahs.v14i4.38
|View full text |Cite
|
Sign up to set email alerts
|

Fournier’s gangrene in the HIV era

Abstract: Background: Fournier's gangrene is a devastating condition that affects mostly patients whose immunity has been reduced. There is increasing evidence for increasing incidence of the disease in those with HIV disease. Objective: To evaluate the presentation, bacteriology and outcome of Fournier's gangrene in our area in recent times in view of the high prevalence in Nairobi and its environs. Results: One hundred and forty six patients were treated for Fournier's gangrene during the study period; all were male. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…This rate of HIV infection is higher than seen in other large studies. Ngugi et al [13] reviewed 146 patients presenting with FG in Kenya and found an HIV rate of 16.4%. Chalya et al [14] reviewed 84 patients with FG in Tanzania and found an HIV rate of 11.3%.…”
Section: Discussionmentioning
confidence: 99%
“…This rate of HIV infection is higher than seen in other large studies. Ngugi et al [13] reviewed 146 patients presenting with FG in Kenya and found an HIV rate of 16.4%. Chalya et al [14] reviewed 84 patients with FG in Tanzania and found an HIV rate of 11.3%.…”
Section: Discussionmentioning
confidence: 99%
“…It showed HIV may be emerging as an important predisposing factor for Fournier's Gangrene. 9 Fournier's gangrene mainly involves perineal region most commonly scrotum. Scrotal involvement along with medial thigh, anterior abdominal wall suggest severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The mortality from studies done in other African countries range from 3.6% to 24%. [7,8,9] A recent 3 year review study on 20 patients from Saudi Arabia recorded zero mortality. [10] They attributed the good prognosis to the moderate severity of their cases and aggressive radical surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…In similar study to ours HIV infection has overtaken diabetes mellitus (16% vs 11%) as the commonest underlying risk factor. [9] The HIV epidemic potentially opens a huge population at risk of developing Fournier's gangrene in sub Saharan Africa. The presence of HIV infection is not a significant factor associated with non-survival similar to findings by Elem and colleagues.…”
Section: Discussionmentioning
confidence: 99%